Exploring the experiences of individuals living with persistent pain using a visual art diary. (September 2022) - Lou, Jasmine; Pourkazemi, Fereshteh; Mackenzie, Lynette
Introduction: Persistent pain significantly impacts daily living. Visual arts interventions can have positive outcomes, but little is known about benefits for people with persistent pain. This study aimed to explore participant experiences of utilising visual art in expressing and managing their persistent pain experience through a visual diary. Method: As part of a small exploratory study nested in a larger project, participants with a history of persistent pain were recruited from a local pain management clinic. Six participants with persistent pain attended five weekly intervention sessions involving art observation, creation and discussion, at the Art Gallery of NSW. Participants explored their ideas about their pain experience through artmaking using visual and written data from self-reported pain diaries. Thematic analysis was used. Results: Analysis of five diaries was conducted. Visual and written expressions of the pain experience varied. Colour was used by participants to represent ideas and emotions. Capital letters were used to convey tone, or emphasis. Three main themes emerged from the written and visual data: 'The lived experience of pain', 'The powerful drive for growth beyond change itself' and 'Personal values and perceptions guiding daily living and decision-making'. Conclusion: This study provides insights into the potential benefits of using visual arts to help manage persistent pain experiences and improve health outcomes.